Socio-Epidemiological and Clinical-Laboratory Characteristics of Patients with HIV and Chronic Hepatitis B+D - Yastrebova, E. B.; Trishina, A. G.; Romanova, S. Yu; Vinogradova, T. N. (Zhurnal infektologii, 2025)
The hepatitis B virus (HBV) and the disease it causes have been actively studied for over 50 years. Recent estimates provided by the World Health Organization indicate that approximately 1 in 22 (4.5%) individuals with chronic hepatitis B have antibodies to the hepatitis D virus (HDV). The exact global prevalence of hepatitis D remains unclear due to differences in the sensitivity and specificity of diagnostic tests and the lack of standardized testing systems. In Russia, patients with hepatitis D are not subject to mandatory registration, and the routes of transmission are similar to those of hepatitis B. The disease is often diagnosed at a late stage (e.g., liver cirrhosis) due to the lack of widespread targeted screening for HDV antibodies among HBsAg-positive patients; about two-thirds of patients are unaware of their infection status. The study of socio-epidemiological and clinical-laboratory characteristics of HIV-positive patients co-infected with chronic hepatitis B and delta agent is of significant scientific and practical interest.The aim of this study was to conduct a comparative analysis of socio-epidemiological and clinical-laboratory features of HIV-positive patients with chronic hepatitis B and delta agent compared to patients without HIV infection. Materials and Methods. The study included 50 patients under observation at the city AIDS center, of whom 24 were diagnosed with HIV infection and chronic hepatitis B+D (Group 1), and 26 had chronic hepatitis B+D without HIV infection (Group 2). The mean age of the patients was 46.7±0.5 years, with 34 males (68.0%) and 16 females (32.0%).Results and Discussion. The “social profile” of HIV-positive patients with chronic hepatitis B+D is characterized as follows: these individuals are typically intravenous drug users, lack higher education, are unemployed, not in formal marriages, and have an HIV infection duration of more than 8 years, often with stage 4A HIV infection according to the Russian classification. All patients in this group were receiving antiretroviral therapy, and the vast majority were also on antiviral therapy for chronic hepatitis. Conclusion. Thus, HIV-positive patients with chronic hepatitis B+D significantly differ from those with chronic hepatitis B+D alone in terms of infection routes, education level, marital status, disease duration, aminotransferase levels, and hematological abnormalities. In both groups, severe liver fibrosis (F3-F4) predominated, accounting for a total of 70%. Antiviral therapy for chronic hepatitis B+D using bulevirtide represents a promising direction for the elimination of HBV and HDV and requires further study and analysis.